Characterisation of Biodiesel Derived From Waste Cotton Seed Oil and Waste Mustard Oil - Singh, Sandeep; Sharma, Sumeet; Mohapatra, S. K.; Kundu, K. (Asian Journal of Engineering and Applied Technology, 2013)
Biodiesel, an alternative fuel is derived from the fats of animals and plants. As energy demand increases and fossil fuels are limited, research is directed towards alternative renewable fuels. Properties of waste oil (cotton seed oil and mustard oil) have been compared with the properties of petrodiesel, showing a comparable regime for satisfactory optimized blend which is to be selected for the better performance of a C.I. engine with biodiesel. The work presented in this paper is the study of characteristics of biodiesel prepared from vegetable oils (waste cotton seed oil and waste mustard oil). The characteristics of biodiesel are to be checked at different blends(B10, B15, B20) and select the optimum blend based on these characteristics. The characteristics include free fatty acid value, density, viscosity, flash point and fire point, cloud point and pour point, carbon residue content and ash residue content.